The Use of Forbidden Materials in Medicinal Products: An Islamic Perspective - Muhammad Mustaqim Mohd.Zarif; Abd Hamid Abd Murad; Arif Fahmi Md Yusof (IDOSI Publications, 2024)
The issue of permissible and forbidden materials found in the production and consumption of medicinal products has generated serious debates among Muslims in the present day. Despite the general prohibition from using forbidden material in any medicinal product, there are also cases where it is permitted. Amidst this divergence of opinions among religious scholars on the matter, this paper aims to analyse this issue in a comprehensive manner from the perspectives of the jurists, Muslim medical practitioners and modern interpretations of the Islamic Law as exemplified by the Fatwa Council of a modern day Muslim country. The study employs qualitative research methods comprising historical and content analysis in developing a holistic understanding of the issue under discussion. The findings explicate the religious and legal basis of using forbidden materials that can provide a guideline on understanding its use in the medical and health aspects.